Synthesis process dependent physico-chemical and opto-electronic properties of Cu2FeSnS4 nanoparticle films. Issue 19 (1st October 2021) - Mukurala, Nagaraju; Mokurala, Krishnaiah; Kumar, Ajit; Kushwaha, Ajay K.; Jin, Sung Hun
Abstract: The present work reports a comparative study of synthesis process-dependent physicochemical, optical, electrical, and photodetective properties of earth-abundant quaternary Cu2 FeSnS4 (CFTS) nanoparticle-based films. CFTS nanoparticles are synthesized via solvothermal and monoethanolamine-assisted hydrothermal processes. X-ray diffraction (XRD) and Raman spectroscopy analyses confirm the phase purity of the synthesized particles. FE-TEM, FE-SEM, and energy-dispersive X-ray spectroscopy (EDS) results demonstrate the formation of smaller particles (~5–10 nm) with stoichiometric chemical composition and larger particles (~100 nm) with Cu-deficient chemical composition in hydrothermal and solvothermal processes, respectively. The optical bandgaps of the hydrothermal and solvothermal-processed CFTS nanocrystalline-based films are calculated to be 1.56 and 1.48 eV, respectively. The temperature-dependent electrical properties of the CFTS nanocrystalline films are analyzed by the transfer length method. The electrical conductivity of hydrothermally and solvothermally synthesized CFTS nanoparticle-based films increased from 31.02 ± 4.04 and 3.12 ± 0.69 mS/cm to 67.73 ± 5.84 and 17.62 ± 2.62 mS/cm, respectively, with an increase in the measuring temperature from 298 to 373 K. The temperature-dependent charge transport properties are attributed to the thermal activation of defects in the CFTS films. The hydrothermally synthesized CFTS nanoparticle-based visible photodetectors exhibited photoinactive properties. The solvothermally synthesized CFTS nanoparticle-based devices exhibited maximum photosensitivity of (21 ± 4) %, photoresponsivity of 128 ± 6 mA/W, and detectivity of 4.68 ± 0.86 × 10 9 Jones. The present study shows that the synthesis process significantly affects the morphology, chemical composition, optical properties, electrical properties, and performance of CFTS nanoparticle-based visible photodetectors. Highlights: Synthesis process dependent physicochemical and opto-electronic properties of CFTS NPs. Chemical composition affects the opto-electronic, photodetective properties of CFTS NPs. Temperature dependent charge transport is explained thermally activated defects in CFTS. Maximum Rph = (128 ± 6) mA/W), Dph = (4.68 ± 0.86) × 10 9 Jones for CFTS visible PDs.